Kualitas Tidur dan Aktivitas Fisik Berkontribusi dengan Tekanan Darah pada Lansia Hipertensi di Dusun Ngepos, Kecamatan Srumbung - Ariyani, Genduk Ita; Erjinyuare Amigo, Thomas Aquino; Lidya, Herlin (STIKes Panti Rapih, 2024)
This study aims to evaluate the relationship between sleep quality and physical activity patterns with blood pressure in elderly hypertensive patients in Ngepos Hamlet. Hypertension is one of the global targets for reducing the prevalence of non-communicable diseases, with the aim of reducing the incidence by 33% between 2010 and 2030. Sleep quality is measured based on quantitative and qualitative aspects, while physical activity is assessed from the intensity of body movements that require energy. The results showed that most elderly hypertensive patients in Ngepos Hamlet had poor sleep quality (98.1%), while only 1.9% had good sleep quality. Most elderly people do heavy physical activity (66.7%), followed by moderate activity (31.4%), and light activity (2%). The gamma correlation test showed that there was no significant relationship between sleep quality and blood pressure (p = 0.306) and between physical activity patterns and blood pressure (p = 0.291) in elderly hypertensive patients. Therefore, it is recommended that elderly people routinely check their blood pressure, participate in integrated health post-activities, maintain sleep quality, and do physical activity according to their abilities.